Measuring Intangible Assets in an Emerging Market Economy : An Application to Brazil - Dutz, Mark A.; Kannebley, Sérgio Jr.; Scarpelli, Maira; Sharma, Siddharth (World Bank, Washington, DC, 2012)
This paper measures intangible investment in Brazil. It estimates that during 2000-2008, annual business spending on intangible assets or knowledge-based capital in Brazil averaged about 4 percent of gross domestic product. While this is significantly lower than comparable rates for the United States, Japan and the United Kingdom, which hover around 11 percent, it is not too far below estimates for other developed countries such as Italy and Spain. Of the total expenditure on intangible assets in 2006, about 23 percent was spent on computer software and databases, 43 percent on innovative property (predominantly research and development and new product development in financial services), and 34 percent on economic competencies (which comprises branding, employee training and organization improvement). Brazil's share of spending on economic competencies is markedly lower than that observed in the United States and the United Kingdom, and the analysis finds it to be the slowest growing of the major intangible categories. Finally, having extended the intangible investment estimation methodology to produce more disaggregated (industry-level) estimates, the authors show that intangible investment is positively correlated with recent export growth and total factor productivity estimates across manufacturing industries. This suggests that intangible or knowledge-based capital, as measured here, can account for part of the hitherto unexplained component of productivity growth.